2012
DOI: 10.1080/1331677x.2012.11517516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Company’s Size on Takeover Success

Abstract: R especting the fact that vast number of M&As do not achieve planed synergies and results and that M&A success is affected by different organizational variables like management, strategy, structure, corporate culture, company size etc., the main aim of this paper is to analyze the impact of company's size on takeover success. Successful takeover is defined as takeover in which target company performs better in the period after the takeover than in the period before the takeover. Hypothesis according to which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…It is important to note that every method used in research on the M&A success has both its advantages and disadvantages and surveying method was used within this research because of the character of observed variables which included strategy, organizational structure, and corporate culture. Measuring instrument (questionnaire) for testing the hypotheses of this research is composed of a set of questions that the respondents including board members and company managers answered and indicated their agreement/disagreement with suggested statements whereat a Likert measurement scale of five degrees was used (Filipović, 2012). Propositions used in various measurement scales are either initially progressed for research purposes, or managed and adapted from existing measurement scales that can be found in the applicable scientific literature (Filipović, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to note that every method used in research on the M&A success has both its advantages and disadvantages and surveying method was used within this research because of the character of observed variables which included strategy, organizational structure, and corporate culture. Measuring instrument (questionnaire) for testing the hypotheses of this research is composed of a set of questions that the respondents including board members and company managers answered and indicated their agreement/disagreement with suggested statements whereat a Likert measurement scale of five degrees was used (Filipović, 2012). Propositions used in various measurement scales are either initially progressed for research purposes, or managed and adapted from existing measurement scales that can be found in the applicable scientific literature (Filipović, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Measuring instrument (questionnaire) for testing the hypotheses of this research is composed of a set of questions that the respondents including board members and company managers answered and indicated their agreement/disagreement with suggested statements whereat a Likert measurement scale of five degrees was used (Filipović, 2012). Propositions used in various measurement scales are either initially progressed for research purposes, or managed and adapted from existing measurement scales that can be found in the applicable scientific literature (Filipović, 2012). In the first part of the questionnaire general data about research participants (position within the company, gender, age, education, working experience), general data about the target (target's name, industry, size), and general data about the acquirer (domestic or international, legal entity or private person) were gathered.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for large acquired firms, they experienced no change or improvements in the pre-acquisition stage when being cp0ompared with non-acquired firms and no significant productivity improvements in the stage of post-acquisition. Filipovic (2012) [48] mentioned in his study that a large number of merger and acquisition transactions do not result in synergies planned and that merger and acquisition are impacted directly by different variables like strategy, management, corporate culture, structure, company size and others. The researchers tested the effect of a firm's size on the success of the takeover.…”
Section: Impact Of Company's Size On Acquisition Successmentioning
confidence: 99%